The inequality impacts of the carbon tax in China - Shuyang Chen (Humanities & Social Sciences Communications, 2022)
Abstract Previous research has acknowledged that climate change is likely to expand the wealth gap, and climate policies may further increase inequality. Nevertheless, little research has focused on how climate policies affect inequality. To address this, we employ a Computable General Equilibrium (CGE) model to quantify the inequality impacts of the Chinese carbon taxes. Our CGE model results show that tax impacts on inequality are influenced by distribution of climate damages, tax payments, and recycling of tax revenues. Specifically, a positive correlation between income and climate damage induces lower inequality, compared to a zero or negative correlation. Tax payments by high-income households induce lower inequality than tax payments proportional to or independent from income. Recycling tax revenues to low-income households only induces lower inequality than the other recycling schemes. The results imply that relative utility is determined by absolute income, whereas income inequality only has a slight impact on it. In other words, governments could reduce negative feelings about inequality under a climate policy by increasing national income, even if the climate policy may induce higher inequality.